2016
DOI: 10.1093/jxb/erw153
|View full text |Cite
|
Sign up to set email alerts
|

Response of chickpea (Cicer arietinumL.) to terminal drought: leaf stomatal conductance, pod abscisic acid concentration, and seed set

Abstract: HighlightExposed to terminal drought, the soil water content at which chickpea seed set ceased coincided with that at which stomatal conductance began to decrease and pod abscisic acid concentration increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 29 publications
11
85
0
1
Order By: Relevance
“…It is worth noting that the percentage of decrease in dry weights was significantly higher for the sensitive variety. Earlier studies demonstrated significant reduction in shoot dry weights when grown under drought conditions in chickpea (Pang et al, ) and in corn (Anjum et al, ). Silvente, Sobolev, and Lara () attributed the decrease in dry weight under drought in the sensitive soybean variety to the depletion of sucrose in the leaves of this variety.…”
Section: Discussionmentioning
confidence: 94%
“…It is worth noting that the percentage of decrease in dry weights was significantly higher for the sensitive variety. Earlier studies demonstrated significant reduction in shoot dry weights when grown under drought conditions in chickpea (Pang et al, ) and in corn (Anjum et al, ). Silvente, Sobolev, and Lara () attributed the decrease in dry weight under drought in the sensitive soybean variety to the depletion of sucrose in the leaves of this variety.…”
Section: Discussionmentioning
confidence: 94%
“…Chickpea is the third most important grain legume (pulse) globally and the largest pulse crop in Australia (FAOSTAT, 2016). It is a primary crop in several developing countries, contributing significantly to human food and animal feed (Foyer et al, 2016;Pang et al, 2017b). In countries such as India, a substantial area of chickpea is grown on marginal and submarginal lands with limited P availability, and P deficiency is one of the major constraints to increasing chickpea productivity (Srinivasarao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is accordance with those of Ahmed et al (2013) and Liu et al (2015) observed reduction in water potential when crop was imposed under drought environment. Water stressed plants showed a significant reduction in leaf water potential than non-water stressed plants (Pang et al 2016).…”
Section: Water Potential (-Mpa)mentioning
confidence: 88%